Catalog Rhetoric as Nation-Building: A Textual Analysis of Smithsonian Anthropology Analog Records - Sorensen, Amanda H. (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2024)
This case study is a close reading of knowledge organization systems against US state politics, exploring the use of place names within museum records as an ontological practice that furthers and perpetuates nation-building. Throughout this paper, I explore the following question: do the paper records analyzed act as nation building tools and, if so, how? I draw on archival research methods, and textual analysis methods stemming from communication studies to analyze a selection of records, ledger book entries and catalog cards, that document a collection of Northwest Coast materials given to the Smithsonian in 1862 by George Gibbs, a surveyor and naturalist. I ultimately argue that ledger book entries and catalog cards in question (as authored by the Smithsonian) serve as nation-building tools that contribute to the development of a US national identity, and further the dispossession of Indigenous lands by obscuring Indigenous sovereignty.